Turnover intention, job satisfaction and workload in ship crew workers: a systematic literature review - Her Fin; Christian Harito; Cipto Purwanto (Publikasi Indonesia, 2024)
Turnover is an activity that harms company operations. Turnover is related to job satisfaction, which is influenced by the level of workload balance. Based on this relationship, the company must formulate a strategy for the factors influencing these three aspects. Previous research has explored influencing factors regarding turnover, job satisfaction, workload, a combination of two variables, or involving all three variables. Previous research has involved these three variables, but the recommendations from previous research still need to be more optimal (turnover still occurs). Therefore, researchers need to analyze gaps and trends from previous research. This will help future research to develop more optimal strategies. Gap and trend analysis in this study used a systematic literature review (SLR) with the PRISMA reporting method. Search results through the SCOPUS database produced seventeen articles. The results of the SLR analysis show that most research was conducted in Africa, oriented to the health sector, and used qualitative methods.